Chromosome end protection by RAP1-mediated inhibition of DNA-PK - Patrik Eickhoff; Ceylan Sonmez; Charlotte E. L. Fisher; Oviya Inian; Theodoros I. Roumeliotis; Angela dello Stritto; Jörg Mansfeld; Jyoti S. Choudhary; Sebastian Guettler; Francisca Lottersberger; Max E. Douglas (Nature, 2025)
Abstract During classical non-homologous end joining (cNHEJ), DNA-dependent protein kinase (DNA-PK) encapsulates free DNA ends, forming a recruitment platform for downstream end-joining factors including ligase 4 (LIG4) 1 . DNA-PK can also bind telomeres and regulate their resection 2–4 , but does not initiate cNHEJ at this position. How the end-joining process is regulated in this context-specific manner is currently unclear. Here we show that the shelterin components TRF2 and RAP1 form a complex with DNA-PK that directly represses its end-joining function at telomeres. Biochemical experiments and cryo-electron microscopy reveal that when bound to TRF2, RAP1 establishes a network of interactions with KU and DNA that prevents DNA-PK from recruiting LIG4. In mouse and human cells, RAP1 is redundant with the Apollo nuclease in repressing cNHEJ at chromosome ends, demonstrating that the inhibition of DNA-PK prevents telomere fusions in parallel with overhang-dependent mechanisms. Our experiments show that the end-joining function of DNA-PK is directly and specifically repressed at telomeres, establishing a molecular mechanism for how individual linear chromosomes are maintained in mammalian cells.